2010
DOI: 10.5391/jkiis.2010.20.4.569
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy r-minimal Preopen Sets And Fuzzy r-M Precontinuous Mappings On Fuzzy Minimal Spaces

Abstract: We introduce the concept of fuzzy r-minimal preopen set on a fuzzy minimal space. We also introduce the concept of fuzzy r-M precontinuous mapping which is a generalization of fuzzy r-M continuous mapping, and investigate characterization of fuzzy r-M precontinuity. In this paper, we introduce the concept of fuzzy  -minimal preopen sets and study some related properties. We also introduce the concept of fuzzy -M precontinuous mappings, which is a generalization of fuzzy -M continuous mapping. In particular,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The concepts of fuzzy -open sets and fuzzy -M continuous mappings are also introduced and studied. In [3], We introduced the concepts of fuzzy -minimal preopen sets and fuzzy -M precontinuous mappings, which are generalizations of fuzzy -minimal open sets and fuzzy -M continuous mappings, respectively. Yoo et al introduced the concepts of fuzzy -minimal compactness, almost fuzzy -minimal compactness and nearly fuzzy -minimal compactness on fuzzy  -minimal spaces in [6].…”
Section: Intorductionmentioning
confidence: 99%
“…The concepts of fuzzy -open sets and fuzzy -M continuous mappings are also introduced and studied. In [3], We introduced the concepts of fuzzy -minimal preopen sets and fuzzy -M precontinuous mappings, which are generalizations of fuzzy -minimal open sets and fuzzy -M continuous mappings, respectively. Yoo et al introduced the concepts of fuzzy -minimal compactness, almost fuzzy -minimal compactness and nearly fuzzy -minimal compactness on fuzzy  -minimal spaces in [6].…”
Section: Intorductionmentioning
confidence: 99%
“…Any union of m-preopen sets is m-preopen [1]. The m-pre-closure and the m-pre-interior of A, denoted by mpCl(A) and mpInt(A), respectively, are defined as the following: ( …”
Section: A ⊆ Mint(mcl(a))mentioning
confidence: 99%
“…They showed that the M -continuous mappings have properties similar to those of continuous mappings between topological spaces. We introduced the concepts of m-preopen set and M -precontinuity on spaces with minimal structures in [1]. In this paper, we introduce the concepts of M -preclosed graph and M * -preopen mapping on spaces with minimal structures and investigate some properties of M * -preopen mapping.…”
Section: Introductionmentioning
confidence: 99%